Climatic risks to adaptive capacity - Olivia Serdeczny; Marina Andrijevic; Claire Fyson; Tabea Lissner; Inga Menke; Carl-Friedrich Schleussner; Emily Theokritoff; Adelle Thomas (Mitigation and Adaptation Strategies for Global Change, 2024)
Abstract Does climate change influence if societies will be better or worse equipped to reduce climatic risks in the future? A society's adaptive capacity determines whether the potential of adaptation to reduce risks will be realized. Assumptions about the level of adaptive capacity are inherently made when the potential for adaptation to reduce risks in the future and resultant levels of risk are estimated. In this review, we look at the literature on human impacts of climate change through the lens of adaptive capacity. Building on evidence of impacts on financial resources as presented in the Working Group 2 (WG2) report of the Intergovernmental Panel on Climate Change (IPCC) Sixth Assessment Report (AR6), we here present the methodology behind this review and complement it with an analysis of climatic risks to human resources. Based on our review, we argue that climate change itself adds to adaptation constraints and limits. We show that for more realistic assessments of sectoral climate risks, assumed levels of future adaptive capacity should — and can — be usefully constrained in assessments that rely on expert judgment, and propose avenues for doing so.
Keywords: 330; Adaptive capacity; Adaptation feasibility; Residual risks; Expert-based judgment